2021
DOI: 10.1021/acs.inorgchem.1c01026
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Investigations into and Control of Anisotropic Metal–Organic Framework Growth

Abstract: The porphyrinic metal−organic framework, PCN-222, exhibits anisotropic growth behavior to form nanorods and microrods with aspect ratios 3 < x < 94. Control of microrod aspect ratios has been demonstrated through the identification of several factors that dictate crystal growth, particularly the concentrations of a ligand, a modulator, and an exogenous base. An increase in the local concentration of a deprotonated ligand, which is proportional to the nucleation rate, is associated with smaller crystals, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 97 publications
(182 reference statements)
1
11
0
Order By: Relevance
“…The modulators selected have all been previously used for the synthesis of UiO-66 and have a range of pK a values in DMF (AA pK a = 13.6, FA pK a = 11.6, DFA pK a = 7.5, and TFA pK a = 6.0). 52,53 The zirconiummodulator bond strength and concentration of the deprotonated modulator available for binding are largely dependent on modulator pK a , and the impact of the modulator on the defect level and particle size has largely been attributed to the acidity of the modulator. 6,7,54 Modulators were screened over the same concentration range; however, at high concentrations of DFA and TFA, reaction yields were significantly reduced.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The modulators selected have all been previously used for the synthesis of UiO-66 and have a range of pK a values in DMF (AA pK a = 13.6, FA pK a = 11.6, DFA pK a = 7.5, and TFA pK a = 6.0). 52,53 The zirconiummodulator bond strength and concentration of the deprotonated modulator available for binding are largely dependent on modulator pK a , and the impact of the modulator on the defect level and particle size has largely been attributed to the acidity of the modulator. 6,7,54 Modulators were screened over the same concentration range; however, at high concentrations of DFA and TFA, reaction yields were significantly reduced.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…To investigate the impact of the modulator on the properties of UiO-66, four commonly used modulators, AA, FA, DFA, and TFA, were chosen for our screening study. The modulators selected have all been previously used for the synthesis of UiO-66 and have a range of p K a values in DMF (AA p K a = 13.6, FA p K a = 11.6, DFA p K a = 7.5, and TFA p K a = 6.0). , The zirconium-modulator bond strength and concentration of the deprotonated modulator available for binding are largely dependent on modulator p K a , and the impact of the modulator on the defect level and particle size has largely been attributed to the acidity of the modulator. ,, Modulators were screened over the same concentration range; however, at high concentrations of DFA and TFA, reaction yields were significantly reduced. At high concentrations of DFA and TFA, the reaction is dominated by the formation of modulator-capped zirconium clusters that outcompete terephthalic acid, and no MOF formation occurs beyond 50 equiv …”
Section: Resultsmentioning
confidence: 99%
“…MOFs are crystalline coordination polymers composed of metal clusters bridged by multidentate organic ligands, resulting in one-, two-, or three-dimensional porous networks. The high porosity leads to the extremely low density exhibited by MOFs; for example, MIL-53-NH 2 and PCN-222 have densities of 0.35 and 0.52 g/cm 3 , respectively, , substantially lower than most of the conventional fillers such as clay (2.9 g/cm 3 ) and cellulose (1.5 g/cm 3 ) . The low density in turn leads to lightweight materials that, due to the other properties of MOFs, may possess multifunctionality and postsynthetic modification capability. , Therefore, MOFs have been incorporated into polymers to form composite materials for a variety of applications such as gas separation, water purification, and toxic chemical degradation. , In addition, MOFs can possess either isotropic or anisotropic growth behaviors depending on metal–linker composition and connectivity as well as synthetic parameters. , Tuning anisotropic growth of MOF particles has been a topic of recent interest in fields such as gas separation and catalysis. We have recently demonstrated the tunability of AR and length for a zirconium-based porphyrinic MOF, PCN-222 (Zr 6 (μ 3 -O) 8 (OH) 8 (TCPP) 2 , where TCPP = meso -tetrakis­(4-carboxyphenyl)­porphyrin) . A wide range of AR was achieved (3.4 to 54) by facilitating anisotropic growth in the longitudinal direction ( c -axis, Figure a), during which the surface chemistry and elemental composition of PCN-222 remain constant.…”
Section: Introductionmentioning
confidence: 99%
“…67−69 We have recently demonstrated the tunability of AR and length for a zirconium-based porphyrinic MOF, PCN-222 (Zr 6 (μ 3 -O) 8 (OH) 8 (TCPP) 2 , where TCPP = mesotetrakis(4-carboxyphenyl)porphyrin). 70 A wide range of AR was achieved (3.4 to 54) by facilitating anisotropic growth in the longitudinal direction (c-axis, Figure 1a), during which the surface chemistry and elemental composition of PCN-222 remain constant. Consistent chemistry, and therewith consistent surface chemistry in the resulting MOFs, is critical for retaining particle−matrix interactions and the mechanical properties of PCN-222.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Such anisotropic growth behavior is consistent with previous reports on other MOF systems, where modulators and other capping agents preferentially attach to specific crystal facets. 56,57 Given that the crystal morphology has a possible impact on the mass transport and the external surface area of the crystallite, we investigated the hydrolysis of the nerve agent simulant dimethyl 4-nitrophenyl phosphate (DMNP) with two types of NU-1008 crystals with distinct aspect ratios, 1.13 and 9.7 (samples 2 and 8 in Figure S7), and found that these two types of crystals display drastically different catalytic hydrolysis performance (Figure 3c; see the Supporting Information for details of the test method). From pseudo-first-order kinetics for short or long NU-1008 samples, the initial rate constant k is 0.782 or 0.0554 min −1 with a half-life of 1.2 or 18 min, respectively, resulting in an enhanced catalytic factor of 15.…”
mentioning
confidence: 99%